(Corridor - Place) As A Comprehensive Approach for Street Pedestrianization: Case Studies in Cairo, Egypt - Nesma Fadda; Mariam Abdullah (JES: Journal of Engineering Sciences, 2025)
Nowadays urban planning trends of walkability and sustainable mobility hope to reintroduce human-scale development in cities and strengthen communities, and one approach that has achieved a growing amount of popularity is the pedestrianization of commercial streets. These streets have the potential to be pleasant places for people to travel through and to visit while achieving sustainability goals at the same time. The design of theses streets especially in developing countries such as Egypt is a key factor that contributes to flourishing economy and better quality of urban life. However, currently, there are no street environments that are pedestrian-friendly and that integrate both the social and physical functions of the street. This research develops a comprehensive 'Corridor-Place' approach for commercial street pedestrianization, integrating the street's dual functions. Employing a mixed-methods analysis—field observation, surveys, questionnaires, and in-depth interviews—the study evaluates the applicability of pedestrianization on two Egyptian commercial streets. The aim is to establish replicable urban quality criteria, encompassing location, accessibility, diversity, and physical and visual attributes, for transforming these streets into sociable and walkable areas. Ultimately, this framework seeks to provide a model for successful pedestrianization projects.